The Influence Of Product And Service Quality On Customer Satisfaction At Tirta Jeneberang Regional Water Company (PDAM) In Gowa Regency - Rahmat Herman; Buyung Romadhoni; Sherry Adelia Natsir Kalla (International Journal of Economic Research and Financial Accounting, 2024)
This research is a quantitative descriptive study aimed at understanding and analyzing the Influence of Product and Service Quality on Customer Satisfaction at the Tirta Jeneberang Regional Water Company (PDAM) in Gowa Regency. The methods used in the research include observation, questionnaires, and documentation. The population and sample used in this study consist of 94 respondents, with data analysis performed using multiple linear regression analysis processed with the aid of Statistical Product and Service Solutions (SPSS) Version 27 software. Based on the results of this study, the t-test results obtained for variable (X1) against variable (Y) show that the t-value is greater than the t-table value, with a calculated value of 4.396 > 0.202 and a significance value of 0.001, which is less than the alpha value of 0.05 (0.001 < 0.05). From these values, it can be concluded that variable (X1) has a positive and significant effect on variable (Y) at the Tirta Jeneberang Regional Water Company (PDAM) in Gowa Regency.  Similarly, the t-test results for variable (X2) against variable (Y) show that the t-value is greater than the t-table value, with a calculated value of 9.723 > 0.202 and a significance value of 0.000, which is less than the alpha value of 0.05 (0.000 < 0.05). From these values, it can be concluded that variable (X2) has a positive and significant effect on variable (Y) at the Tirta Jeneberang Regional Water Company (PDAM) in Gowa Regency.